Peran Hukum Ekonomi Syariah dalam Pembangunan Ekonomi Berkelanjutan - Elsa Julia; Ulfa Dwi Yanti; Imam Al Hamdi (CV. ITTC INDONESIA, 2024)
Sustainable economic development is the main goal for many countries in this era of globalization. This concept not only calls for steady economic growth, but also requires the adoption of practices that address social justice and environmental sustainability. Sharia economic law offers a unique framework for achieving this goal, by integrating the principles of distributive justice, sustainable management of natural resources, and economic empowerment through mechanisms such as zakat and sadaqah. This article examines in depth the role of sharia economic law in the context of sustainable economic development. Through a case study approach from countries such as Malaysia, Indonesia and the United Arab Emirates, we analyze the positive impact of implementing sharia economic law on financial inclusion, environmental management and community empowerment. Our findings show that sharia economic law is not only relevant in the Muslim context, but also has the potential to make a significant contribution to creating a more equitable, inclusive and sustainable economy in various global contexts. In conclusion, this article emphasizes that further integration of sharia economic law principles can be an effective strategy for countries that wish to optimize economic growth while paying attention to environmental sustainability and social justice. Thus, sharia economic law is not only an alternative, but also an integral part of sustainable economic development in the future.